Risk Factors of Parvovirus in Dogs at De' Lab Pet Clinic, Bekasi - Harelas, Genoveva Callista; Arimbi, Arimbi; Hamid, Iwan Sahrial; Praja, Ratih Novita; Yunita, Maya Nurwartanti (Jurnal Medik Veteriner, 2022)
This study aimed to determine the percentage of parvovirus, risk factor analysis, and describe the symptoms and treatment of parvovirus. The study was conducted by surveying, collecting secondary data from patient medical records and Bekasi City's rainfall data, data recording, data unification, and data analysis. Data analysis was presented descriptively and tested using Chi-Square and Odds Ratio (OR). The results shows the percentage of parvovirus was 2%. The rainfall factor <150mm/month significant to the risk of parvovirus (p<0,05) and increase the risk of parvovirus 0,154 times. The age factors 0-6 month significant to the risk of parvovirus (p<0,05) and increase the risk of parvovirus 0,017 times. The breed factors not significant to the risk of parvovirus (p>0,05) and don't increase the risk of parvovirus. The main symptoms seen in parvovirus include vomiting, diarrhea especially bloody diarrhea, and fever. The main components treatments are fluid therapy, antibiotic, antiemetic, and nutritional support. The administration of other drugs can be given to dogs whose administration must be adjusted to their respective conditions.